2020
DOI: 10.1186/s12888-020-2430-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: The Japanese version of the questionnaire about the process of recovery: development and validity and reliability testing

Abstract: After publication of our article [1] we were notified that the 5-point Likert-type scale in Additional file 1 needs to change from “1 to 5” to “0 to 4”. The updated Additional file 1 is included in this correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Previous studies indicated that recovery-promoting factors include close relationships, social support, and positive support from mental health services [8,9]. In our study, in addition to support and recoveryoriented practices, which were also found in previous studies, having positive childhood experiences was extracted as an original recovery-promoting factor in our study.…”
Section: Recovery-promoting Factorssupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies indicated that recovery-promoting factors include close relationships, social support, and positive support from mental health services [8,9]. In our study, in addition to support and recoveryoriented practices, which were also found in previous studies, having positive childhood experiences was extracted as an original recovery-promoting factor in our study.…”
Section: Recovery-promoting Factorssupporting
confidence: 77%
“…Previous studies indicated that recovery-promoting factors include close relationships, social support, and positive support from mental health services [8,9]. In addition to those themes, the theme of positive childhood experiences was extracted in our study.…”
Section: Recovery-promoting Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A shortened version of 15 items of the QPR (QPR-15) showed better psychometric properties than the original version ( Law et al, 2014 ). The original English version has been validated in Chinese ( Chien and Chan, 2013 ), Swedish ( Argentzell et al, 2017 ), and Japanese ( Kanehara et al, 2017 , 2020 ), and the 15-item version has been adapted in Spanish (QPR-15-SP) ( Goodman-Casanova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, programs aimed toward recovery similar to those developed in the west, such as Assertive Community Treatment, Wellness Recovery Action Plan, Illness Management and Recovery, and Recovery College are widely practiced in Japan [10][11][12][13][14]. For the evaluation of practice, the psychometric properties of the Japanese version of recovery-related scales in which service users measure their personal recovery and service providers measure their recovery knowledge and attitude have been verified [15][16][17][18][19][20]. As described above, programs including personal recovery are being used.…”
Section: Introductionmentioning
confidence: 99%